Perspectives of healthcare professionals on facilitators, barriers and needs in children with obesity and their parents in achieving a healthier lifestyle - Naomi de Pooter; Emma van den Eynde; Hein Raat; Jacob C. Seidell; Erica L.T. van den Akker; Jutka Halberstadt (PEC Innovation, 2022)
Objective: To explore the perspectives of healthcare professionals (HCPs) within an integrated care approach on the facilitators, barriers and needs in children with obesity and their parents in achieving a healthier lifestyle. Methods: Semi-structured interviews were conducted with eighteen HCPs working within a Dutch integrated care approach. The interviews were analyzed by performing a thematic content analysis. Results: Main facilitators identified by HCPs were support from parents and the social network. Main barriers were first and foremost family’s lack of motivation, which was singled out as a precondition for starting the behavior change process. Other barriers were child’s socio-emotional problems, parental personal problems, lack of parenting skills, parental lack of knowledge and skills regarding a healthier lifestyle, parental lack of problem awareness and HCP’s negative attitude. To overcome these barriers, main needs that HCPs suggested were a tailored approach in healthcare and a supportive HCP. Conclusion: The HCPs identified the breadth and complexity of underlying factors of childhood obesity, of which the family’s motivation was pointed out as a critical factor to address. Innovation: Understanding the patient’s perspective is important for HCPs to provide the tailored care needed to address the complexity of childhood obesity.